Studi Kesiapan Konsep Personal Higiene pada Masyarakat Menuju Desa Wisata Edukasi Kulinologi - Muhammad Prasetya Kurniawan; Novita Erma Kristanti; Mohammad Wahyudin; Wildan Fajar Bachtiar; Annisa Dwi Astari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
ABSTRACT The identification of the community's readiness to develop their capability from farming to culinary to support food security needs understanding and awareness about personal hygiene. Observations, interviews, and questionnaires were used to determine 100 respondents from 8 sub villages in Banyusoco, Playen, Gunungkidul. The level of knowledge, understanding, and awareness of self-hygiene is explored from the implementation of socialization, the impact of dissemination and training activities, the frequency of hand washing before handling food, the frequency of handwashing with soap or disinfectant after using the toilet, at the dining area, and time for at least 20 seconds use of soap. Readiness analysis is also reviewed from the level of education. The results of identification show that daily habits that affect consciousness are needed. However, further research and dissemination are needed to explain the differences between behavioral reports, abilities, and awareness.Keywords: dissemination, practice, knowledge, consciousness, personal hygiene